Core-shell heterostructure-enabled stress engineering in vanadium dioxide nanobeams. (December 2021) - Shin, Ki Hoon; Bae, Ji Yong; Lee, Su Yong; Ahn, Docheon; Cho, Jiung; Yoon, Jongwon; Hong, Woong-Ki; Sohn, Jung Inn
Highlights: A core-shell heterostructure for engineering phase transition pathways and properties in VO2 has been demonstrated. A core-shell heterostructure was fabricated by the formation of a very thin Al2 O3 shell layer on VO2 nanobeams using atomic layer deposition. A simple, direct, and abrupt metal-insulator transition property without stress and phase inhomogeneities in core-shell VO2 nanobeams was demonstrated. The distinct phase transition property of core-shell VO2 nanobeams was investigated by temperature-dependent phase evolution and computational finite element analyses of stress states. Abstract: In strongly correlated materials (SCMs), especially for vanadium dioxide (VO2 ), manipulating physical properties through stress engineering is an important issue for the use of ultrafast metal-insulator transition (MIT) in device applications. Recent research efforts have mainly focused on modulation and related phenomena of physical properties by epitaxial and mechanical stresses in VO2 films or anisotropic nanocrystals. However, inhomogeneous stress in such planar and nanocrystal systems leads to complications induced by phase competitions or the creation of intermediate phases. Here, we demonstrate the core-shell heterostructures-enabled stress engineering on MIT, which provides accommodation of uniform axial stress and control of phase transition pathways in VO2 nanobeams. Specifically, the VO2 nanobeams with an amorphous Al2 O3 shell undergo a simple and direct MIT at lower temperatures without intermediate phases, distinctly different from pristine nanobeams with coexisting phases. For the core-shell nanobeams, the VO2 core sustains a uniform compressive stress state along the nanobeam length caused by shell formation, which can be attributed to the different thermal behaviors coupled to the elastic modulus between the VO2 and shell. Our results can lead to better engineering of phase transitions in SCMs, providing the beneficial effect of suppressing inhomogeneities during the MIT process. Graphical abstract: Image, graphical abstract